Does the ASEAN-Japan Comprehensive Economic Partnership cause trade creation and trade diversion? - Rossanto Dwi Handoyo, Gayatri Talita Aprilia, (Opción, 2020)
The establishment of ASEAN-Japan Comprehensive Economics Partnership or AJCEP create an economic cooperation between Japan and the member of ASEAN countries also trading partner of AJCEP. The purpose of this study is to find out trade creation effect and trade diversion effect in Indonesia’s export with the AJCEP member countries and trading partner because of AJCEP agreement. Moreover, there were several factors, which influence the total export positive or negative, such as GDP and exchange rate that influence positively in Indonesia’s export, also the distance between both country which trade and income difference per capita negatively influence in Indonesia’s export.